Rozwój profesjonalny dyrektora szkoły – przesłanki dla rozwiązań instytucjonalnych - Rosalska, Małgorzata (Studia Edukacyjne, 2020)
The goal of this article is to reflect on the relationship between theoretical assertions of leadership in education and practical solutions for the education of human resources in the management of education. There are being analyzed proposals for institutional development opportunities that determine the effective performance of tasks, both managerial and leadership ones, assigned to the school principal. To this end, the current forms of professional development offered to school principals and the theoretical underpinnings of the system for promoting the professional development of school community leaders are presented.